Analisis Pengaruh Kualitas Produk, Harga, dan Citra Merek Terhadap Kepuasan dan Loyalitas Konsumen Safina Fried Chicken - Didip Diandra (Jurnal Ekonomi, 2017)
This research aims to analyze of the influence Product Quality, Price, and Brand Image to Customer Satisfaction and the effects to Customer Loyalty on Safina Fried Chicken at Cipinang Muara Jatinegara. Purposive sampling method has been selected to obtain data requires at this study. The research use 50 respondents and respondent’s entire customer Safina Fried Chicken at Cipinang Muara. Path Coefficient analysis used as analytical method in this research. The result of this research shows that: Product Quality, Price, and Brand Image have significant influence on Customer Satisfaction and finally affect the Customer Loyalty simultaneously and partially. The only have dominant influenced to customer satisfaction among all variables was brand image.